Essentials of nuclear chemistry - Arnikar, H.J. ([S.l.] : New Age International Pvt. Ltd, 2010)
The revised edition retains the essential theories of nuclear structure and stability, radioactivity and the principles of fission, fusion and breeder reactors of the earlier editions. The preparation of the more commonly used radioisotopes and their uses as tracers in research, medicine, agriculture and industry are described. The book also covers the elements of Radiation and Radiochemistry illustrated with additional examples. The section on Mossbauer effect is retained. The chapter on the detection and measurement of radioactivity is revised to include thermoluminescence and Cerenkov detectors.
Keywords: nuclear chemistry